Peran ASN Mengajar Aceh dalam Membimbing Perilaku Anak-Anak dari Keluarga Pemulung untuk Mencapai Kesejahteraan Hidup - Zahratul Aflakh; Kusmawati Hatta; Azhari Azhari (Journal of Society Counseling, 2026)
Children from waste-picker families may have limited access to supplementary learning and supportive developmental environments. This study analyzes the role of ASN Mengajar Aceh in guiding children’s behavior to support the attainment of well-being. A descriptive qualitative design was used, involving semi-structured interviews with seven adult volunteers or administrators and three child participants aged 9–13 years. Adult and child data were analyzed separately using thematic analysis and then compared to identify convergence, divergence, negative cases, and unavailable evidence. The program provided non-formal education through Fun Learning, literacy and numeracy, talent-interest activities, creative business activities, and educational outings. Guidance was integrated into learning through personal, humanistic, and family-like approaches, modeling, habituation, advice, play, practice, and positive reinforcement. Adults perceived indications of improvement in motivation, politeness, discipline, confidence, and basic skills, although one adult reported that behavioral change was not clearly visible. Children described enjoyable activities, positive relationships, creative interests, and diverse aspirations. The program therefore contributes mainly to nonmaterial well-being through education, social attention, creativity, motivation, relationships, and aspirations; improvements in household economic well-being were not established.